Antidiarrhoeal Activity of Dalbergia Sissoo Leaves in Goats - Amrutkar, Y. K.; Hajare, S.W.; Sontakke, A. R.; Bhojane, N. M.; Ingole, R. S.; lngawale , M. V. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
Antidiarrhoeal activity of Leaves of Dalbergia sissoo (D. sissoo) was evaluated in mice using castor oil induced diarrhoea and gastrointestinal motility test with charcoal meal method and further in clinical cases of goats. The results showed that the D. sissoo leaves extract (400 mg/kg and 800 mg/kg) produced significant (,o<0.01) reduction in frequency of defecation up to 75.12% compared to control mice in castor oil induced diarrhoea. The inhibition of charcoal meal transit by D. sissoo at dose of 400 mg/kg and 800 mg/kg treated groups was found to be 42.95 and 53.20 per cent, respectively as compared to controls. In clinical cases of diarrhoea in goats D. sissoo decoction treated group showed complete recovery and normalization of the faeces on 4th day of treatment. The study revealed that D. sissoo possesses potent antidiarrhoeal activity.